Risks of Endurance Training in Minors - A Narrative Review - Tomasik, Jan T.; Bochenek, Michał S.; Dubiel, Mikołaj; Kolano, Sylwia Wiktoria; Wańczyk, Daria; Filip, Kinga; Gródek, Aleksandra; Jakubowski, Wojciech (International Journal of Child Health and Nutrition, 2026)
Background: Participation in endurance sports among children and adolescents is increasing. Pediatric athletes differ physiologically from adults due to ongoing somatic growth, biological maturation, and endocrine development, which modify both adaptive responses and injury susceptibility. Aim: This review synthesizes current evidence on physiological adaptations to endurance training in youth and examines the major musculoskeletal, cardiovascular, metabolic, endocrine, and psychosocial risks associated with high training loads. Materials and Methods: A narrative review of literature published between January 1990 and January 2026 was conducted using PubMed and MEDLINE, supplemented by consensus statements from major sports medicine organizations. Results: Endurance performance improvements in youth are influenced more by neuromuscular maturation than by large central cardiovascular adaptations, with modest training-induced changes in VO₂ max before puberty. The developing musculoskeletal system demonstrates high adaptive plasticity but increased vulnerability to overuse injuries, including physeal stress injuries and bone stress injuries. Inadequate energy availability may disrupt endocrine function and impair growth and bone development. Conclusions: While endurance training promotes beneficial physiological adaptations, the developing athlete remains vulnerable to overuse injuries, low energy availability, psychosocial stressors, and long-term health risks. Recognition of these mechanisms is essential for accurate risk interpretation and safe training practices.